Penerapaan Metode TOPSIS dengan Pembobotan ROC dalam Seleksi Penerimaan Auditor Internal Perusahaan - Rima Tamara Aldisa (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
Cheating or fraud is a major problem that must continue to be routinely monitored at the company. Fraud is a form of fraud that is carried out intentionally by hiding a truth or fact so that it can incite other people to commit acts that are detrimental to the company. In preventing fraud at the company, routine audit activities must be carried out at the company with a fast and precise time. For the company's operational system to be better, the audit activity is carried out by an internal auditor. Internal auditors are someone who works in activities with confidence with the aim of being able to advance values and improve company operations in an objective and independent manner. In the selection of candidates for internal auditors, there are several criteria as an internal auditor that have been determined by the company, namely General Knowledge, Skills, Expertise Certificates, Personal Qualities, Traits and Education. Currently the company does not have a system that can carry out the selection of appropriate and objective internal auditor candidates. The selection of internal auditors is carried out objectively, so the authors use a decision support system (SPK). SPK is an information system that functions as an aid in decision making within an organization. This system is useful in solving problems encountered through the use of predetermined methods. In this study, the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method and the ROC (Rank Order Centroid) method were used to obtain the data needed in the selection of internal auditor candidates to get Ratih Budi with a score of 1.0000 in alternative A6 as an internal auditor. on the company.